Sentic Computing Techniques, Tools, and Applications - Cambria, Erik.; Hussain, Amir.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2012)
In this book common sense computing techniques are further developed and applied to bridge the semantic gap between word-level natural language data and the concept-level opinions conveyed by these. In particular, the ensemble application of graph mining and multi-dimensionality reduction techniques is exploited on two common sense knowledge bases to develop a novel intelligent engine for open-domain opinion mining and sentiment analysis. The proposed approach, termed sentic computing, performs a clause-level semantic analysis of text, which allows the inference of both the conceptual and emotional information associated with natural language opinions and, hence, a more efficient passage from (unstructured) textual information to (structured) machine-processable data.
Keywords: Medicine; Data mining; Mathematics; Consciousness; Biomedicine; Biomedicine general; Data Mining and Knowledge Discovery; Mathematics, general; Linguistics (general).; Cognitive Psychology